Pengembangan UMKM (Inovasi Pembuatan Kerupuk Kelapa Bersama Masyarakat Jorong Pemukiman Baru II Sebagai Peluang Usaha Dalam Meningkatkan Ekonomi Masyarakat) - Anita, Anita Khairani; Seri Hanida, Rahmi; Munawwir Nasution, Ahmad; Lailatul Jannah; Aisyaturriadho; Tiara Adelina; Patimah Sari; Arda Lestari; Nanda Mulia Riski; Muhammad Panogu (LPPI UMN AL WASHLIYAH, 2024)
Jorong Pemukiman Baru II is a village in West Pasaman Regency, West Sumatra. This village has abundant coconut potential but has not been utilized optimally. Coconuts in this village are still sold in raw form and have not been processed into value-added products. The main problem that the author encountered was the lack of innovation in coconut processing to improve the community's economy. Therefore, the aim of carrying out this activity is not only to carry out work programs during the KKN period, but also to develop innovation in making coconut-based crackers as a new business opportunity that can improve the economy of the community, especially in Jorong Pemukiman Baru II. This activity involves training in making coconut crackers, from processing raw materials to marketing strategies. The method the author uses is the science and technology diffusion method, which involves the application of new technology and knowledge in the process of making coconut crackers. Data collection techniques include direct observation and product testing, with qualitative analysis to evaluate training effectiveness and product quality. With optimal use of coconut and the right marketing strategy, coconut crackers can become a superior product that contributes to the welfare of the community, especially in Jorong Semukiman Baru II and the development of UMKM in the village.